Fermented Broth in Tyrosinase- and Melanogenesis Inhibition - Chan, Chin-Feng (Molecules, 2014)
Fermented broth has a long history of applications in the food, pharmaceutical and cosmetic industries. Recently, the use of fermented broth in skin care products is in ascendance. This review investigates the efficacy of fermented broth in inhibiting tyrosinase and melanogenesis. Possible active ingredients and hypopigmentation mechanisms of fermented broth are discussed, and potential applications of fermented broth in the cosmetic industry are also addressed.